Competition, investment reversibility, and equity risk premium - Zhang, Zhou (Journal of Banking & Finance, 2023)
This paper investigates the role of investment reversibility in determining the relationship between product market competition and equity risk premium. We develop a unified real-option framework involving corporate investment and disinvestment decisions in a continuous-time Cournot–Nash equilibrium. The effect of competition on a firm’s risk premium induced by contraction options is negative and similar to that on the risk premium induced by expansion options; however, for assets in place, more competition results in a higher risk premium by increasing operating leverage. Notably, investment reversibility rather than product market demand moderates the competition-risk premium relationship. Our model predicts that the equity risk premium is more negatively correlated with the level of competition if investments are more reversible because firms are more likely to adjust their capacity in response to uncertain demand and this flexibility attenuates the positive operating leverage effect. We find robust empirical evidence to support our theoretical prediction.